The Action Phurpa (’phrin las phur pa) from the Eightfold Buddha Word, Embodying the Sugatas (bKa’ brgyad bDe gshegs ’dus pa), revealed by Nyang-rel Nyima Özer (1124–1192, Tib. myang ral nyi ma ’od zer) - Cantwell, C (Ruhr-Universität Bochum, 2020)
This paper presents the main findings of an in-depth textual study of the core sections of the “’phrin las phur pa [Action Phurpa]” part of Nyang-rel Nyima Özer’s (Tib. Myang ral Nyi ma ’od zer) revealed corpus of the bKa’ brgyad bDe gshegs ’dus pa [The Eightfold Buddha Word, Embodying the Sugatas]. This research suggests that at least this part of the Eightfold Buddha Word revelation represents the survival of an archaic form of practice on the tantric deity, Vajrakīlaya. Its six sections constitute a coherent whole covering complementary aspects of the tantric rituals, while the second section parallels in its entirety a text from the archaeological recovered manuscripts from a Library Cave in Dunhuang (IOL Tib J 331.III), which dates back over a century before Nyang-rel’s time. Here, a critical edition of that second section of Nyang-rel’s Action Phurpa is presented, taking account of all current extant versions, and supported by consideration of the accompanying materials found in the five other sections.